ATEX-Explosive Atmospheres Risk Assessment, Control and Compliance - Jespen, Torben; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book details how safety (i.e. the absence of unacceptable risks) is ensured in areas where potentially explosive atmospheres (ATEX) can arise. The book also offers readers essential information on how to comply with the newest (April 2016) EU legislation when the presence of ATEX cannot be avoided. By presenting general guidance on issues arising out of the EU ATEX legislation - especially on zone classification, explosion risk assessment, equipment categorization, Ex-marking and related technical/chemical aspects - the book provides equipment manufacturers, responsible employers, and others with the essential knowledge they need to be able to understand the different - and often complicated - aspects of ATEX and to implement the necessary safety precautions. As such, it represents a valuable resource for all those concerned with maintaining high levels of safety in ATEX environments.
Workplace Legislation -- Risk parameters -- ATEX - Prevention -- ATEX - Equipment selection -- ATEX - Mitigating measures -- ATEX - Risk Assessment -- Zone Classification - Oil Fluids -- Zone Classification - Natural Gas -- Zone Classification - Dusts -- ATEX - Worldwide -- ATEX - Equipment Regulation -- ATEX - Ignition Hazard Assessment (IHA) -- ATEX - Ignition Sources -- ATEX - Communicating IHA Results -- ATEX - Ex-marking -- Fires and Explosions.
Keywords: Law -- Europe; Security systems; Chemicals -- Safety measures; Manufactures; European Law; Security Science and Technology; Chemical Safety; Machines, Tools, Processes